2011
DOI: 10.1002/chem.201003014
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Orthogonal Self‐Assembly of a Synergetic Gelator System

Abstract: exhaustively developed over the past two decades, [1,2] however the recent interest for advanced functional nanomaterials has made this area of research particularly exciting.[3] Organogels based on low molecular weight organic gelators (LMWOGs) are formed by self-assembled fibrillar networks (SAFINs), which are produced by a combination of weak non-covalent physical interactions including hydrogen bonding, p-p stacking, dipole-dipole or donor-acceptor interactions, metal coordination and van der Waals interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…There are a number of examples for both mixed and self-sorted systems where the rheological properties are improved compared to what might be expected from the individual components. 78,86,91,100,101 Even from these relatively few examples however, it is clear that there is not a simple link between the rheological data and the type of assembly.…”
Section: Conclusion Challenges and Opportunities For Multi-component ...mentioning
confidence: 99%
“…There are a number of examples for both mixed and self-sorted systems where the rheological properties are improved compared to what might be expected from the individual components. 78,86,91,100,101 Even from these relatively few examples however, it is clear that there is not a simple link between the rheological data and the type of assembly.…”
Section: Conclusion Challenges and Opportunities For Multi-component ...mentioning
confidence: 99%
“…10 Many LMWG are thermally triggered, assembling into fibres when a hot solution is cooled. 12,17,[20][21][22][23] For example, a mixed LMWG system was thermally gelled, with the final rheological properties being significantly higher than for either LMWG alone. 24 This mechanical reinforcement was explained as being due to co-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Self-sorting in supramolecular gel phases is a rare phenomenon and, at present, always achieved via thermally induced gelation [6][7][8][9][10][11][12] . Typically, a solution containing the two types of gelator molecule is heated above the temperature required to dissolve both completely.…”
mentioning
confidence: 99%
“…On cooling, one molecule assembles at a higher temperature than the other, which can result in a self-sorted network. Formation of such a self-sorted network is often inferred from visual differences between self-assembled structures as imaged by scanning electron microscopy (SEM), atomic force microscopy or transmission electron microscopy (TEM) [6][7][8] . For example, Shinkai and colleagues 5 have demonstrated that a bulk heterojunction can be formed via the thermal self-sorting of two specific gelators that selfassemble to form fibres, with the junctions between fibres giving rise to the heterojunction.…”
mentioning
confidence: 99%